WIC food packages : time for a change (National Academies Press, 2006)
"The Special Supplemental Nutrition Program for Women, Infants, and Children (the WIC program) has promoted the health of low-income families for more than 30 years by providing nutrition education, supplemental food, and other valuable services. The program reaches millions of families every year, is one of the largest nutrition programs in the United States, and is an important investment in the nation s health. The U.S. Department of Agriculture charged the Institute of Medicine with creating a committee to evaluate the WIC food packages (the list of specific foods WIC participants obtain each month). The goal of the study was to improve the quality of the diet of WIC participants while also promoting a healthy body weight that will reduce the risk of chronic diseases. The committee concluded that it is time for a change in the WIC food packages and the book provides details on the proposed new food packages, summarizes how the proposed packages differ from current packages, and discusses the rationale for the proposed packages."--Publisher's description